Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Supporters at headquarters: ??Don Albright, Nick Bronzan, ??, Linda Bronzan, Ruth Wall, Bea Lynch